Academic roots of chemical engineering in XVIII and XIX century in middle Europe - Halasi Tibor; Kalamković Snežana; Cvjetićanin Stanko (Hemijska Industrija, 2010)
Roots of chemical engineering in Middle Europe lead to the first mining and metallurgy academies, established in VIII century in Upper Hungaria and in Bohemian Kingdom. Chemical engineering skills originate from ancient Egyptian handicraft, alchemy, technical chemistry, pneumochemistry and phlogiston chemistry. Development of mining and metallurgy coincided with great scientific discoveries and industrial revolution. In Middle Europe, the first such academies were opened in St. Joachimstahl and in Schemnitz, and the first Serbian mining engineers Djordje Branković, Vasilije Božić and Stevan Pavlović studied, as well as the first chemistry professor of the High School in Belgrade, Mihajlo Rašković. Eminent professors were employed by the Schemnitz academy, such as: Nicol Jacquin, Giovanni Scopoli, Ignaz von Born and Christian Doppler. It is important to emphasize that Shemnitz practiced the first modern, practical laboratory education. In VIII century, Schemnitz Mining and metallurgy academy was the most contemporary educational insistution for engineers. However, in XIX century, mining and metallurgy academies stagnated, due to the replacement of professional academies with polytechnic schools, technical universities and scientific research institutes.